Effect of melatonin on cytokine levels in a hyperthermia-induced febrile seizure model - Aydin, Leyla; Yurtcu, Erkan; Korkmaz, Yeşim; Sezer, Taner; Ogus, Ersin (Cellular and Molecular Biology, 2017)
Higher serum cytokine levels have been reported in children admitted with febrile seizures and in some experimental models. However, other studies have shown that cytokine levels are influenced by melatonin. In this study, we investigated serum cytokine levels in a hyperthermia-induced febrile rat seizure model and the effect of melatonin. A total of 28 male Sprague–Dawley rats were divided into four groups: the control (C) group, healthy melatonin (MT) group, and hyperthermia-induced febrile seizure groups with (HIFS-MT) and without (HIFS) administration of melatonin. Melatonin (80 mg/kg) was given intraperitoneally 15 min before the seizure. HIFS was induced by placing the rats in 45°C water. The rats were sacrificed under anesthesia after the seizure. Blood samples were drawn by transcardiac puncture to measure serum cytokine and melatonin levels. Serum interleukin (IL)-1Î², IL-6, IL-10, and tumor necrosis factor (TNF)-Î± levels were lower in the HIFS group than those in the C group (p = 0.005, p = 0.200, p = 0.011, and p = 0.016, respectively). All serum cytokine levels of rats in the MT and HIFS-MT groups were similar to those in the C group. This experimental rat model demonstrated that serum cytokine levels decrease with HIFS and that administering melatonin maintains serum cytokine levels. These results suggest that cytokines may play role in the anticonvulsive activity of melatonin in rats with febrile seizures.